Characteristic and phylogenetic analyses of mitochondrial genome for Rhinogobius filamentosus (Teleostei: Gobiidae: Gobionellinae), an endemic species in China. Issue 9 (2nd September 2022) - Chen, Xiao Jiang; Song, Lin; Liu, Wen Zhao; Wang, Quan
Abstract: This study sequenced and annotated the complete mitochondrial genome sequence of Rhinogobius filamentosus, an endemic species in China. The complete mitochondrial genome was 16, 510 base pairs long and contained 13 protein-coding genes (PCGs, 11, 414 bp), 22 tRNA genes (1, 555 bp), two rRNA genes (2, 615 bp), two non-coding regions (D-loop: control region displacement loop, 478 bp; OL: origin of L-strand replication, 30 bp). The overall base composition of the genome was estimated to be T (25.4%), C (30.2%), A (27.6%) and G (16.7%), showing an AT bias (53%). Phylogenetic analyses revealed that the genus Rhinogobius included two clades. For one clade, R. filamentosus clustered with R. duospilus, and they formed a sister-group relationship with other ten Rhinogobius species. This work would be essential in revealing the evolutionary relationships in Gobionellinae.